On the dose rate dependence of radiofluorescence signals of natural quartz - Friedrich, Johannes; Fasoli, Mauro; Kreutzer, Sebastian; Schmidt, Christoph (Radiation measurements, 2018)
The general behaviour of the main UV emission during radiofluorescence (RF) in natural quartz with dose rates ranging from 10 to 500 mGy s−1 is analysed. RF emission spectra were recorded and deconvolved to extract information on the C band, which is often the main emission of quartz annealed at a temperature close to 500 °C. Our results confirmed theoretical findings, e.g., the direct proportionality of the initial RF signal of the C band with dose rate and the direct proportionality of the initial slope with the squared dose rate. Furthermore, numerical simulations employing a three-energy-level model and experimental data are in agreement. A first concept of using quartz UV-RF for dosimetric application is given based on the findings that different absorbed doses resulting from different dose rates match well into a single UV-RF decay curve.
Online verfügbar: 1. März 2018, Artikelversion: 22. März 2018
Gesehen am 27.03.2025